Guards! Guards! (Discworld, ,, 2001)
"Here there be dragons... and the denizens of Ankh-Morpork wish one huge firebreather would return from whence it came. Long believed extinct, a superb specimen of draco nobilis ('noble dragon' for those who don't understand italics) has appeared in Discworld's greatest city. Not only does this unwelcome visitor have a nasty habit of charbroiling everything in its path, in rather short order it is crowned King (it is a noble dragon, after all). Meanwhile, back at Unseen University, an ancient and long-forgotten volume-- The Summoning of Dragons-- is missing from the Library's shelves. To the rescue come Captain Vimes, Constable Carrot, and the rest of the Night Watch who, along with other brave citizens, risk everything, including a good roasting, to dethrone the flying monarch and restore order to Ankh-Morpork (before it's burned to a crisp)" --Publisher.

Going postal: a novel of Discworld (Discworld, 33,, 2009)
Suddenly, condemned arch-swindler Moist von Lipwig found himself with a noose around his neck and dropping through a trapdoor into ... a government job? By all rights, Moist should be meeting his maker rather than being offered a position as Postmaster by Lord Vetinari, supreme ruler of Ankh-Morpork. Getting the moribund Postal Service up and running again, however, may prove an impossible task, what with literally mountains of decades-old undelivered mail clogging every nook and cranny of the broken-down post office. Worse still, Moist could swear the mail is talking to him. Worst of all, it means taking on the gargantuan, greedy Grand Trunk clacks communication monopoly and its bloodthirsty piratical headman. But if the bold and undoable are what's called for, Moist's the man for the job - to move the mail, continue breathing, get the girl, and specially deliver that invaluable commodity that every being, human or otherwise, requires: hope.

The Wee Free Men (Discworld, 30,, 2009)
A young witch-to-be named Tiffany teams up with the Wee Free Men, a clan of six-inch-high blue men, to rescue her baby brother and ward off a sinister invasion from Fairyland.

Dodger (HarperCollins, Harper, 2012)
"In an alternative version of Victorian London, a seventeen-year-old Dodger, a cunning and cheeky street urchin, unexpectedly rises in life when he saves a mysterious girl, meets Charles Dickens, and unintentionally puts a stop to the murders of Sweeny Todd"--